Levels of Awareness of Factors Leading to Obesity: A Case of Maamba Old Township in Sinazongwe District of Southern Province, Zambia - Owen Sikumba; Malvern Kanyati; Emmanuel Malichi; Annie Phiri (Asian Journal of Medicine and Health, 2026)
Obesity is a growing public health concern, and community awareness of its contributing factors is important for prevention and health education. This study aimed to evaluate levels of awareness of factors contributing to obesity in Maamba Old Township, Sinazongwe District, Southern Province, Zambia. The objectives were threefold: first, to assess general awareness levels of obesity and risk factors among residents; second, to identify the specific factors that residents are most aware of as contributors to obesity; and third, to propose recommendations for public health campaigns and educational initiatives. The research employed a mixed-methods approach, using both qualitative and quantitative data, with a sample of approximately 380 participants representing diverse segments of the community. The study revealed varying levels of awareness among residents, with discernible differences in the recognition of specific contributing factors. Key factors such as poor diet, overeating, and lack of exercise were commonly acknowledged, reflecting baseline awareness within the community. However, disparities were evident across demographic groups, suggesting the need for targeted interventions. Notably, healthcare professionals demonstrated a higher level of awareness than some occupational groups, highlighting potential areas for focused educational efforts. In conclusion, the research underscores the importance of tailoring public health campaigns to the specific context of Maamba Old Township. The identified disparities in awareness levels require a nuanced approach that acknowledges the influence of diverse factors such as age, occupation, and cultural perspectives. The findings emphasise the need for collaboration among healthcare professionals, community leaders, and residents to design effective awareness strategies. Based on the study outcomes, recommendations include the development and implementation of culturally sensitive public health campaigns. These campaigns should address identified gaps in awareness among specific demographic groups, considering factors such as age and occupation. Additionally, fostering collaboration between healthcare professionals and community members is crucial to the success of educational initiatives. The study calls for ongoing monitoring and evaluation of awareness levels to inform adaptive strategies and support sustained impact.